An air-stable and solution processable tetracarboxydiimide-based materials with tunable charge transport properties. (November 2018) - Daskeviciene, Maryte; Urnikaite, Simona; Planciunaite, Greta; Malinauskas, Tadas; Gruodis, Alytis; Viliunas, Mindaugas; Kamarauskas, Egidijus; Gaidelis, Valentas; Jankauskas, Vygintas; Getautis, Vytautas
Abstract: Novel bipolar molecules based on naphthalene- (V555 ) and perylene- (V565 ) tetracarboxydiimide core, bearing 1-phenyl-1, 2, 3, 4-tetrahydroquinoline end capping hole transporting groups, were designed and synthesized. Electro-optical and thermal measurements, such as UV/VIS, charge mobility, ionization potential, thermogravimetric analysis, and differential scanning calorimetry, were carried out to characterize the new materials. V555 and V565 showed bipolar behavior with both hole and electron mobilities under ambient conditions without any protection from oxygen or moisture. The gelation of V565 was observed that provides the ability to tune the charge transport properties. Graphical abstract: Image 1 Highlights: Imide derivatives based on naphthalene- and perylene- core bearing tetrahydroquinoline end capping groups were synthesized. V555 and V565 show bipolar behavior with both hole and electron mobilities under ambient conditions. The perylenetetracarboxydiimide chromophores forms sandwich-type H-aggregates in V565.